Pemikiran Behaviorisme dan Implementasinya dalam Pendidikan Biologi - Rahmawati Darussyamsu; Jamaris Jamna; Sufyarma Marsidin (Department of Biology Education, Faculty of Education and teacher Training, Maritime University of Raja Ali Haji, 2020)
Philosophy is an inseparable component of education, because philosophy is the foundation of education itself. During its development, there were various framework of philosophy, one is behaviorism. However, various opinions dicredit the use of behaviorism philosophy as a view that is not relevant to the education nowadays. In fact, behaviorism thought has many strengthen among its weakness. This thought is based on the view that education is a change in behavior, which can be changed through direction from educators by repetition of behavior in learning. The advantages of this thinking can be used in various learning materials, one of which is in the subject of biology, because this activity covers the competence of students as a whole. Educators must be selective in using behaviorisme thinking in appropriate learning, in order to optimize the strengths and minimize the weaknesses.